The secretory small GTPase Rab27B as a marker for breast cancer progression. - Hendrix, A. (2010)
In contemporary oncology practice, an urgent need remains to refine the prognostic assessment of breast cancer. It is still difficult to identify patients with early breast cancer who are likely to benefit from adjuvant chemotherapy. Although invasion of cancer cells is the main prognostic denominator in tumor malignancy, our molecular understanding and diagnosis are often inadequate to cope with this activity. Therefore, deciphering molecular pathways of how tumors invade and metastasize may help in the identification of a useful prognostic marker. We recently discovered that the secretory small GTPase Rab27B, a regulator of vesicle exocytosis, delivers proinvasive signals for increased invasiveness, tumor size, and metastasis of various estrogen receptor (ER)-positive breast cancer cell lines, both in vitro and in vivo. In human breast cancer specimens, the presence of Rab27B protein proved to be associated with a low degree of differentiation and the presence of lymph node metastasis in ER-positive breast cancer.